On the L1 Stability to a Generalized Degasperis-Procesi Equation. (6th February 2014) - Yan, Haibo; Yong, Ls; Hu, Hanlei
Abstract : A nonlinear generalized Degasperis-Procesi equation is investigated. Assuming that the strong solution of the equation is bounded in the sense of L ∞ R -norm and the initial data belong to the space L 1 ( R ) ∩ L 2 ( R ), we prove that the solutions are stable in the space L 1 ( R ) .